Green Supply Chain Management: an Analysis of the Supplier-Agro Industry Relationship of a Southern Brazilian Company - Simone Sehnem; Gean Pacheco de Oliveira (BBR: Brazilian Business Review)
This study aimed to analyze the supplier and agro industry relationship regarding the required environmental management practices in the perception of managers. These partners are also called suppl iers or subcontractors. This agro industry exports to about a hundred and ten countries. It is one of the largest private employers in the country and has approximately one hundred and fourteen thousand employees. The study was conducted in only one plant. In this unit there are one hundred and fifty registered suppliers. Six suppliers were selected that provided the greatest number of services for the surveyed unit over the last year of work. It is a case study, descriptive and whose approach is qualitativ e. We found that the main practices carried out in the evaluated companies are in relation to solid waste management. Only two of the companies surveyed have a standardized management and adequate management of the waste generated in their processes. Simil arly, only one company has positive practices in relation to water resources. Therefore, this work can be considered a guide for improving the practices adopted by small and medium - sized suppliers of Alpha. The role of alpha is essential for induction of G reen Supply Chain Management in the supply chain as a whole.